The worth and values of education - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
Since he took over the helms of Singapore’s education ministry after the General Elections in May 2011, first term minister Mr Heng Swee Keat has signalled that he wants a renewed emphasis of character and values education in schools. In his first dialogue session with SMU university students, Heng shared more about his vision for Singapore’s education system.